2020
DOI: 10.1039/d0ra01721c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal cation doping in CeO2 support on catalytic methane steam reforming at low temperature in an electric field

Abstract: Temperature dependence of electron/ion conductivity of Pd/CeO2 and Pd/Al-CeO2 under wet conditions with application of an electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…CeO 2 -based materials have been used for various catalytic reactions 24 including catalysis related to surface protonics in the electric field. 15,17,18 Its utilization is not limited to catalysis. Many researchers have anticipated the usefulness of CeO 2 -based materials as an electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 -based materials have been used for various catalytic reactions 24 including catalysis related to surface protonics in the electric field. 15,17,18 Its utilization is not limited to catalysis. Many researchers have anticipated the usefulness of CeO 2 -based materials as an electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…9, the temperature dependence was different between the dry (Ar) and wet (Ar+H 2 O) conditions, and the conductivity enhancement in the low-temperature region was observed only in the wet condition. This phenomenon can be attributed to the increase of adsorbed water on the grain surface with decreasing temperature, which enhanced the surface proton conduction [79][80][81][82][83][84][85][86][87][88][89][90] . This result is in good agreement with the results of the operando-DRIFTS measurements.…”
Section: Steam Reforming and Dry Reforming Of Methanementioning
confidence: 99%
“…[39][40][41] This active migration is called surface protonics. It has been revealed that surface protonics plays a key role in activating the cleavage of strong bonds, as in the NRN bond in N 2 , [13][14][15][16][17]42,43 and the C-H bond in hydrocarbons, as in CH 4 [42][43][44][45][46] and methylcyclohexane (MCH). 4,5 Those activations make it possible to catalyze hydrogen production and formation of the hydrogen carrier, even at low temperatures (o500 K).…”
Section: Overviewmentioning
confidence: 99%